The food security and quality of life of the households involved in the oyster mushroom project in Maseru, Lesotho - Nkoko, Nthabeleng (University of the Free State, 2020)
Food insecurity and poor quality of life are among the challenges that have delayed development in developing countries. Lesotho is among the African countries that persistently experiences high food insecurity. The country is also faced with poor quality of life, which is indicated by the high prevalence of communicable and non-communicable diseases, poor access to water and sanitation and low household income levels among others. One of the initiatives that aims to improve the household food security and quality of life of the nation, was the introduction of Oyster mushroom cultivation, a project that is sponsored by an external donor in cooperation with the government of Lesotho. This study sought to describe the food security and quality of life of the households involved in the Oyster mushroom project in Maseru, Lesotho. The specific objectives of the study were to describe the quality of life of the households engaged in the Oyster mushroom project; to assess the income of the households involved in theOyster mushroom project; to describe the household food availability of the households involved in the Oyster mushroom project and to report on the household food access of the households engaged in the Oyster mushroom project.A survey was undertaken among the households (n=33) involved in Oyster mushroom cultivation in Maseru. The Statistical Package for Social Sciences (SPSS) version 25.0 was used to analyse the data. Descriptive statistics were used to organise and summarize data to enable interpretation. The descriptive statistics involved frequencies, binomial and Chi-square tests, to support the interpretation of the results. The results indicated a high prevalence of diseases and the need for medical help, which suggests poor quality of life since the percentage of households involved in the Oyster mushroom project (HOMP) that received care from health services, without staying overnight, was high (72.7%). None of the HOMP have medical insurance schemes, because most of them have low income levels. Consequently, HOMP (78.8%) spend part of their income on health related items. Arthritis, high blood pressure, influenza and pain were the main reasons most households bought health related items four weeks prior to the survey.The households do not use energy sources that have a negative effect on health and the environment, such as biomass. The households mainly use Liquefied Petroleum vGas (LPG), electricity and kerosene with more than half (54.2%) using LPG. The responses further indicated that the households experienced a significant lack in quality rather than quantity of available foods. Access to food and money was never experienced as enough, as 15% of the households did not have enough food for three meals every day, although no person had to go a day without food or with only one meal the previous day. Approximately a quarter of the households experienced a severe lack of food. Despite cultivating the mushrooms and having access to it, 69.5% of the households were seasonally food insecure and theirmain income was formal employment, as cultivation was not sufficient. More than half (51.2%) of HOMP have low income levels, one household depends on mushroom production only, the other households get supplementary income from the Oyster mushroom project.Oyster mushrooms are not an indigenous food to Lesotho, therefore acceptance by consumers was limited, resulting in a smaller market than anticipated, and thus the desired increase in income was not seen. Although access and availability was not positively influenced, access to clean water and improved sanitation was better than the majority of the population. For this initiative to be successful, consumers need to be sensitised to the consumption of Oyster mushrooms, stimulating a market for the producers, thereby potentially increasing food security.
Dissertation (M.Sc.Home Ec. (Consumer Science))--University of the Free State, 2020
Keywords: Food security; Food insecurity; Quality of life; Oyster mushroom; Income; Food availability; Food access; Energy; Health; Water and sanitation